2012
DOI: 10.1540/jsmr.48.97
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adaptive relaxation of the rat stomach using an orally inserted balloon instead of surgical intervention by demonstrating the effects of capsaicin and <i>N</i><sup>ω</sup>-nitro-L-arginine methylester

Abstract: Gastric functions such as adaptive relaxation have usually been monitored in rats using a surgically inserted barostat's balloon. However, surgery causes physiological damage to the rat stomach. This study is an investigation of adaptive relaxation of the rat stomach using a slightly modified balloon, which is introduced into the stomach through the mouth of anesthetized rats without the need for balloon surgery, attached to a brostat. In this case, the balloon was placed between the fore-stomach and the fundu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…24,25 However, it is easy to speculate that such a surgical procedure affects the gastric physiological function in an animal study, and that an animal study does not always reflect in vivo and human physiology. We improved the method for investigating gastric adaptive relaxation with the use of a barostat without the need for a surgical procedure, 15 and used this method in the present study. Adaptive relaxation has been known to be mediated by the capsaicin-sensitive afferent nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 However, it is easy to speculate that such a surgical procedure affects the gastric physiological function in an animal study, and that an animal study does not always reflect in vivo and human physiology. We improved the method for investigating gastric adaptive relaxation with the use of a barostat without the need for a surgical procedure, 15 and used this method in the present study. Adaptive relaxation has been known to be mediated by the capsaicin-sensitive afferent nerve.…”
Section: Discussionmentioning
confidence: 99%
“…26 We also reported that nitric oxide (NO) plays an important role in the gastric adaptive relaxation as demonstrated with the use of a barostat. 15 Indeed, NO formed from L-arginine was detected in the murine stomach in vivo. 27 In the present study, L-cysteine, L-aspartic acid and Larginine significantly enhanced the gastric adaptive relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical study, Barostat study was considered to be gold standard for evaluating gastric accommodation. We recently improved the method to evaluate gastric accommodation in rats without surgical operation (7). Then in the present study we used our method for evaluating the effect of Ltryptophan on the gastric accommodation, and found that L-tryptophan significantly enhanced the gastric accommodation.…”
mentioning
confidence: 69%
“…Gastric accommodation was evaluated by the method previously reported by us (7). Rats were anesthetized by urethane (1.2 g/kg, i.p.).…”
mentioning
confidence: 99%